High‐Power Electrochemical Energy Storage System Employing Stable Radical Pseudocapacitors1. (18th December 2013) - Maruyama, Hitoshi; Nakano, Hideyuki; Nakamoto, Masaaki; Sekiguchi, Akira
Abstract The development of electrical energy storage devices that can operate at high charge and discharge rates is fundamentally important, however although electrochemical capacitors (ECs) can charge and discharge at high rates, their electrochemical storage capacity remains an order of magnitude lower than that of conventional lithium‐ion batteries. Novel pseudocapasitors are developed, based on the stable persilyl‐susbtituted free radicals of the heavy group 14 elements, (tBu2MeSi)3E. [E=Si (1), Ge (2), and Sn (3)], as anode materials for energy storage system. Such systems showed a remarkable cycle stability without significant loss of power density, in comparison with similar characteristics of the known organic radical batteries, the dual carbon cell, and the electrochemical capacitor. Particularly important is that these novel electrochemical energy storage systems employing stable heavy group 14 element radicals are lithium‐free. The electrochemical properties and structures of the reduced and oxidized species were studied by the cyclic voltammetry (CV), electron paramagnetic resonance (EPR) spectroscopy, and X‐ray diffraction (XRD).